Preoperative nutritional support for patients undergoing elective colorectal cancer surgery - does it really work? - Tesar, Milan; Kozusnikova, Veronika; Martinek, Lubomir; Durdik, Stefan; Ihnat, Peter (Biomedical papers, 2023)
Aims. This study aimed to evaluate the effect of preoperative administration of oral nutritional supplements (ONS) on the self-sufficiency, physical status, and nutritional status of patients undergoing elective colorectal resections. Methods. This prospective randomized clinical trial was conducted in a single institution. Patients scheduled to undergo colorectal cancer surgery were randomized to either ONS twice per day for 7 days before surgery or no ONS. Results. We enrolled 120 patients in the study. The two study groups had comparable hospital stay times and comparable numbers of postoperative complications. Laboratory parameter (albumin and prealbumin) values declined in the postoperative period, but differences between study groups were not significant. The groups had comparable arm circumference measurements, muscle mass and fat proportions, and water weights. Patient self-sufficiency in the postoperative period was comparable between groups (P=0.313). Lower limb force declined after surgery, but differences between the groups were not significant (P=0.579). Conclusion. Preoperative administration of ONS to patients undergoing elective colorectal surgery did not reduce postoperative morbidity or enhance recovery. Moreover, patient self-sufficiency, physical status, and nutritional status were not influenced by preoperative ONS. Patients should be properly selected for malnourishment before providing nutritional support to manage costs efficiently. Trial Registration: ClinicalTrials.gov (NCT03930888).
Keywords: nutritional supplements; malnutrition; colorectal cancer; self-sufficiency; postoperative morbidity